Broadband anisotropic photoresponse of the “hydrogen atom” version type-II Weyl semimetal candidate TaIrTe4 - Lai, Jiawei (2019)
The layered ternary compound TaIrTe4 is an important candidate to host the recently predicted type-II Weyl Fermions that break Lorentz invariance. Photodetectors based on Weyl semimetal promise extreme performance in terms of highly sensitive, broadband, and self-powered operation owing to its topologically protected band structures. In this work, we report the realization of a broadband self-powered photodetector based on TaIrTe4. The photocurrent generation mechanisms are investigated with power- and temperature-dependent photoresponse measurements. The prototype metal-TaIrTe4-metal photodetector exhibits a responsivity of 20 μA W–1 or a specific detectivity of 1.8 × 106 Jones with 27 μs response time at 10.6 μm. Broadband responses from 532 nm to 10.6 μm are experimentally tested with potential detection range extendable to far-infrared and terahertz. Furthermore, anisotropic response of the TaIrTe4 photodetector is identified using polarization-angle-dependent measurement with linearly polarized light. The anisotropy is found to be wavelength dependent, and the degree of anisotropy increases as the excitation wavelength gets closer to the Weyl nodes. Our results suggest this emerging class of materials can be harnessed for broadband, polarization angle-sensitive, self-powered photodetection with reasonable responsivities.